2009
DOI: 10.1128/iai.01459-08
|View full text |Cite
|
Sign up to set email alerts
|

Perforin and Gamma Interferon Expression Are Required for CD4+and CD8+T-Cell-Dependent Protective Immunity against a Human Parasite,Trypanosoma cruzi, Elicited by Heterologous Plasmid DNA Prime-Recombinant Adenovirus 5 Boost Vaccination

Abstract: A heterologous prime-boost strategy using plasmid DNA, followed by replication-defective recombinant adenovirus 5, is being proposed as a powerful way to elicit CD4 ؉ and CD8 ؉ T-cell-mediated protective immunity against intracellular pathogens. We confirmed this concept and furthered existing research by providing evidence that the heterologous prime-boost regimen using the gene encoding amastigote surface protein 2 elicited CD4 ؉ and CD8 ؉ T-cell-mediated protective immunity (reduction of acute parasitemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
130
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 66 publications
(91 reference statements)
14
130
0
1
Order By: Relevance
“…ϩ T-cell immune responses of these two mouse strains following heterologous prime-boost vaccination, we observed that both mice had similar numbers of splenic specific CD8 ϩ T cells (13). Nevertheless, the CD8 ϩ T cells of the susceptible perforin-deficient mice had functional defects detected by immunological assays performed in vivo and in vitro (13).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…ϩ T-cell immune responses of these two mouse strains following heterologous prime-boost vaccination, we observed that both mice had similar numbers of splenic specific CD8 ϩ T cells (13). Nevertheless, the CD8 ϩ T cells of the susceptible perforin-deficient mice had functional defects detected by immunological assays performed in vivo and in vitro (13).…”
mentioning
confidence: 83%
“…In earlier studies, we described that protective immunity against T. cruzi infection, as measured by reductions in peak parasitemia and delayed mouse mortality, could be achieved by heterologous plasmid DNA priming-recombinant adenovirus boosting vaccination (13). This protective immunity was long-lived.…”
Section: Comparison Of Functional and Phenotypic Aspects Of Transgenementioning
confidence: 99%
See 2 more Smart Citations
“…A estratégia dose-reforço heteróloga, permite a combinação de diversas formas de apresentação do antígeno em um mesmo regime vacinal, (HU et al, 1992;LASARO et al, 2005;DE ALENCAR et al, 2009;RIGATO et al, 2011) Em trabalho realizado por Ciabattini e colaboradores (2004), um regime vacinal do tipo "prime-boost" heterólogo, cujo "prime" foi realizado com esporos de B. subtilis como veículo vacinal vivo, capaz de expressar o fragmento C da toxina tetânica por via de mucosa oral, e o "boost" consistia na administração do mesmo antígeno em sua forma purificada, por via parenteral (subcutânea) resultou em respostas imunológicas antígenos-específicas locais e sistêmicas compatíveis com o correlato de proteção previsto para esta toxina. Apesar de promissor, o regime "prime-boost" heterólogo ainda não foi explorado com antígenos recombinante da proteína P1 de S. mutans, e poderia ser uma boa alternativa para entrega dos antígenos por vias de mucosa em estratégias vacinais contra a cárie.…”
Section: Veículos Vivos Vacinaisunclassified